Sistem Informasi Pengajuan dan Analisis Kelayakan Kredit Berbasis Website Menggunakan Metode AHP Simulasi Pada Bank Perkreditan Rakyat Cibitung - Kusumo, Bayu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Credit is an important instrument in improving the community's economy, providing wider access to capital through financial institutions. Perumda BPR Sukabumi is one of the institutions that offers credit programs to support local economic growth. However, until now, BPR Sukabumi does not have a computerized credit worthiness analysis system, causing the decision-making process for granting credit to be slow and at risk of errors, which can have an impact on company performance and customer satisfaction. This research aims to design and implement a decision support application for credit worthiness analysis using the Analytical Hierarchy Process (AHP) method which is expected to help credit analysts in assessing and recommending the feasibility of granting credit. The AHP method was chosen because of its ability to manage various complex, interconnected criteria in the credit worthiness assessment process, including customer profile, credit history, financial stability and proposed collateral. In this system, the weight of each criterion is analyzed and ranked for more objective and accurate final results. The result of this research is a computer-based application that simplifies the credit worthiness analysis process at BPR Cibitung. With this application, credit analysts can more quickly and accurately assess prospective customers, so that credit decisions can be made more efficiently. This AHP-based application is also expected to be able to reduce the risk of bad credit by identifying potentially high-risk customers. Thus, this application can be a useful tool for improving operational efficiency and the quality of BPR services to its customers